Risk and efficiency analysis of dual mixed refrigerant liquefaction process configurations for floating liquefied natural gas at conceptual design stage - You, Wonwo; Park, Jaeuk; Jung, Seungho; Lim, Youngsub (Process Safety Progress, 2019)
Liquefied natural gas (LNG) floating production storage offloading, or floating liquefied natural gas (FLNG), is an offshore unit used to produce LNG from offshore gas reservoirs. The liquefaction is critical process for liquefying natural gas (NG) into LNG. Among NG liquefaction technologies used in the industry, single mixed refrigerant, dual mixed refrigerant (DMR), and the nitrogen expansion liquefaction process have been considered for FLNG on account of its space limitations and higher safety standards. In particular, the DMR liquefaction process is preferred for a large FLNG because of its high efficiency. Many studies have been suggested about an efficiency of DMR, but a few studies have been conducted on their process safety although different configurations in process concepts can cause meaningful differences in operating conditions and safety. In this study, two DMR process configurations were optimized to maximize the efficiency and conceptual explosion risk was analyzed to compare their risk at the conceptual design stage. The results showed a difference between the explosion risks by the differences in the optimal mixed refrigerant compositions and number of devices, with similar efficiencies. These results can provide insight for a risk management strategy at the conceptual design stage, to minimize the unexpected cost generation. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 38: 87–98, 2019.
Keywords: Conceptual design stages; Explosion risk; Floating production storage offloading; Liquefaction process; Liquefied Natural Gas (LNG); Process configuration; Process safety; Risk management strategies; conceptual design; DMR liquefaction process; explosion risk analysis; floating liquefied natural gas; process safety